2015
DOI: 10.1186/s13071-015-0691-y
|View full text |Cite
|
Sign up to set email alerts
|

Repellent and insecticidal efficacy of a new combination of fipronil and permethrin against three mosquito species (Aedes albopictus, Aedes aegypti and Culex pipiens) on dogs

Abstract: BackgroundThree laboratory studies were conducted to assess the repellent and insecticidal efficacy of a combination of fipronil and permethrin (Frontline Tri- Act®/Frontect®) against three mosquito species (Aedes albopictus, Aedes aegypti and Culex pipiens) on dogs.MethodsIn each study, 16 healthy adult dogs were allocated to two groups. Eight dogs were treated with the new topical spot-on combination of fipronil and permethrin on Day 0 and the other eight dogs served as untreated controls. Each dog was expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
1
22
2
Order By: Relevance
“…In the current study, the feeding rate of S. albopicta on control mice ranged between 41.4 and 52.8% and was slightly higher than that reported in a previous dog study (24.4–50.6%) using the same mosquito species (Fankhauser et al ., ). The high feeding rate showed that the population of S. albopicta in the experiment was robust (the mosquito population did not suffer any abnormality as a result of taking a bloodmeal from mice), which allowed the effect of the anti‐feeding product to be validated.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In the current study, the feeding rate of S. albopicta on control mice ranged between 41.4 and 52.8% and was slightly higher than that reported in a previous dog study (24.4–50.6%) using the same mosquito species (Fankhauser et al ., ). The high feeding rate showed that the population of S. albopicta in the experiment was robust (the mosquito population did not suffer any abnormality as a result of taking a bloodmeal from mice), which allowed the effect of the anti‐feeding product to be validated.…”
Section: Discussionmentioning
confidence: 97%
“…() using the same formulation against S. aegypti in dogs. However, repellency was close to that reported for other commercial products containing permethrin tested against S. albopicta in dogs (Fankhauser et al ., ). Permethrin is both an insecticide and a repellent.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations